IN SILICO STUDY: THE POTENTIAL OF KILEMO (Litsea cubeba) ENDEMIC PLANT FROM KALIMANTAN AS ANTI-BREAST CANCER THROUGH HER2 INHIBITION - Utami, Dwi; Elmaningtyas Zahro, Tarisha; Nisa, Khairun; Farid, Muhammad (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Breast cancer is the most common cancer in the world with high complication and mortality rates. Overexpression of human epidermal growth factor receptor-2 (HER2) is one of the mechanisms of breast cancer. Kilemo plant (Litsea cubeba) contains compounds such as naringenin, ellagic acid, caffeic acid, ferulic acid, and syringic acid, which can inhibit the overexpression of HER2. This research is a preliminary study of the development of the plant as an anti-breast cancer natural drug candidate through a molecular docking study. The method used in the molecular docking of kilemo compounds with the protein kinase domain of human HER2. Firsly, the preparation of proteins and test ligands, followed by validation of the docking method with redocking. The compounds was testing the interaction of with proteins and analyzing and visualizing results using Autodock-4 and Biovia Discovery Studio, compounds was the evaluation of pharmacokinetic predictions. The results showed that the compounds contained have good affinity for the protein kinase domain of human HER2. Naringenin and ellagic acid have the best potential with the binding energy of -8.60 kcal/mol and -7.76 kcal/mol, with inhibition constants of 493.67 µM and 2.05 µM. Pharmacokinetic predictions of the six compounds fulfill the requirements of oral drug candidates. Although the binding affinity of all tested compounds were lower than lapatinib, but based on toxicity prediction, the compounds are not as hepatotoxic as Lapatinib. In conclusion, the plant has potential to be developed as a traditional medicine candidate for natural anti-breast cancer drugs that are safer than lapatinib.